"Servicification of Manufacturing - Evidence from Swedish Firm and Enterprise Group Level Data" - Magnus Lodefalk (Örebro University School of Business, 2010)
The manufacturing industry in industrialised countries is often argued to servicify - use and sell more services - but knowledge is poor. We examine the phenomenon using detailed and com-prehensive micro level data at both the firm and enterprise group level for Sweden (1997-2006). We find that manufacturing is servicifying substantially. Services and qualified services are increasingly characterising in-house activity in manufacturing. The results imply that treat-ing services and manufacturing separately - for instance in trade policy negotiations - may be inappropriate in industrialised countries. Finally, the findings illustrate the value of enterprise group level data when studying structural economic changes.
Keywords: F14; L16; 330; servicification; manufacturing; deindustrialisation; enterprise group level data; firm data; outsourcing; offshoring